Changes of Physical Properties during Microwave Processing of Sagon. Issue 3 (24th September 2012) - Ghani, N.A.; Yusof, Y.A.; Talib, R.A.; Chin, N.L.; Aziz, M.G.
Abstract This study was designed to investigate the best and efficient method of processing sagon, a traditional snack food, using a microwave oven. Microwave cooking was conducted at three output powers of 90, 170 and 340 W. The effects of salt and different formulations on physical (moisture, water activity, color, surface morphology) as well as sensory properties of sagon were also investigated. Microwave heating reduced the time of cooking and/or drying compared with that of conventional way. The color of sagon was solely dependent on microwave output power and sugar content; the higher the output power the lesser is lightness and the greater is redness and yellowness, but texture and surface roughness showed better at medium microwave heating (170 W) confirmed by the micrographs. Microwave processing of sagon having high sugar content (60%) in the formulation at rather higher output power (340 W) resulted in most preferred sagon compared with that of conventional one available in the local market. Addition of salt bought about slightly higher reading of water activity and moisture content. Practical Applications Sagon is a traditional food among Malay community, which represents the specialty and variety of Malaysian culture. Although the popularity of sagon is quite in decline in the present busy Malay society, the simplified and modernized processing techniques may aid in getting back its popularity. Sagon is prepared by mixing its ingredients followed by gentle heating, which is tedious and time consuming. In this study, this laborious and conventional heating in preparing sagon had been replaced with modern processing systems like microwave cooking. It is well‐known that microwave processing and cooking of foods is a recent development and it is convenient, rapid, high energy efficient and easy to handle. In the present study, microwave processing of sagon was found quite convenient and rapid, and resulted in most preferred sagon than that of traditional one available in the local market. This study will help to conserving traditional recipe.